La filosofía del Dr. Serge Raynauld de la Ferriere y su influencia en el desarrollo psicosocial de los niños de cinco años de la Unidad Educativa Básica Invesciencias - Sánchez Huacón, Ericka Pamela (2015)
The following investigation distinguishes the psychosocial ambit and the interaction capacity of the children with the environment that surrounds them. One of the most important theories about the psychosocial developing focuses in the training and integration of the child inside the society, it´s based in the Serge Raynaud de la Ferrier’s Theory, that proposes some different ways in order to the professional educators can influence in the children that are five years old with the initiative of integrating and helping them to solve psychological conflicts with a positive attitude in the environment that interferes directly in their psychosocial development. The educative community doesn`t reduce only in the teaching of the scientist knowledge, it`s relevant that children must get skills and develop a critical thinking in order to search and process information that let them integrating in the environment that it´s harder and more competitive every time…..